EFFECT OF PLACENTAL CRYOEXTRACT ON SCAR TISSUE FORMATION AFTER ELECTIVE SURGERY IN PATIENTS WITH MORNING CHRONOTYPE - Toropov, O.A.; Lychman, V.O.; Steblovskyi, D.V.; Boiko, I.V.; Bukhanchenko, O.P.; Yatsenko, P.I.; Ivanytska, O.S. (World of Medicine and Biology, 2024)
In the realities of today, the number of maxillofacial injuries is growing every day, which increases the number of people who visit maxillofacial surgeons, which in turn leads to an increase in the percentage of pathological scarring. Previous studies have shown that the formation of scars after surgery is also influenced by a person's chronotype. Circadian rhythms play a fundamental role in the regulation of basic functions in the human body, such as changes in body temperature, hormone secretion, cognitive and physical abilities, etc. Placental cryo-extract has a positive effect on wound healing throughout the entire treatment period. The main factor is the chronotype of a person, so in people with a morning biorhythm who underwent surgery in the first half of the day, the indicators are better than in patients who underwent surgery in the second half of the day.
Keywords: cryopreserved placenta; scar; chronotype; extract; skin; biological rhythms